Fas Polymorphisms Influence Susceptibility to Autoimmune Hepatitis - Hiraide, Akira; Imazeki, Fumio; Yokosuka, Osamu; Kanda, Tatsuo; Kojima, Hiroshige; Fukai, Kenichi; Suzuki, Yoichi; Hata, Akira; Saisho, Hiromitsu (The American journal of gastroenterology, 2005)
Genetic factors associated with autoimmune hepatitis (AIH) and primary biliary cirrhosis (PBC), immune-mediated chronic inflammatory liver diseases of unknown etiology, remain to be elucidated. Polymorphisms of the gene encoding Fas have been linked to a variety of autoimmune diseases. We hypothesized that Fas gene polymorphisms might be genetic markers for AIH and PBC. To determine the frequency and significance of Fas polymorphisms in patients with AIH and PBC, 74 Japanese AIH patients, 98 Japanese PBC patients, and 132 ethnically matched control subjects were investigated by the use of the Taqman assay. We found significant differences between AIH patients and controls in allele frequencies of Fas-670 (p=0.009), Fas IVS (intervening sequence) 2nt176 (p=0.018), Fas IVS3nt46 (p=0.031), and Fas IVS5nt82 (p=0.013) polymorphisms. Haplotype analysis revealed that one of the haplotypes, GATGC, was associated with increased AIH prevalence. On the other hand, we found no statistically significant differences between PBC patients and controls in allele frequencies of the Fas polymorphisms genotyped in this study. These results indicate a genetic link of Fas polymorphisms to the development of AIH. Further studies are needed to determine the genetic factors contributing to the development of AIH.